2019
DOI: 10.1021/acsomega.9b01731
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength, Low-Permeable, and Light-Protective Nanocomposite Films Based on a Hybrid Nanopigment and Biodegradable PLA for Food Packaging Applications

Abstract: Herein, a multifunctional filler, a dye (organic)–clay (inorganic) hybrid nanopigment (DCNP), was embedded into polylactic acid (PLA) to fabricate a colored biodegradable/biocompatible film, which is explored as a high thermomechanical resistant as well as a superior light and mass transport barrier for food packaging applications. In this respect, the DCNP was synthesized through a wet chemical process with a reaction yield of 76% and incorporated into a PLA matrix at various concentrations using a solution c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 68 publications
0
34
0
Order By: Relevance
“…By adding GO, the permeability of the membranes increased by ~8% compared to the PLA film. This could be due to the good dispersibility of GO in the PLA matrix, making the membranes more hydrophilic [ 50 , 51 , 52 , 53 ]. Liu et al [ 44 ] also demonstrated that the surface wettability of electrospun composite fiber mats is enhanced by the GO and/or nanohydroxyapatite inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…By adding GO, the permeability of the membranes increased by ~8% compared to the PLA film. This could be due to the good dispersibility of GO in the PLA matrix, making the membranes more hydrophilic [ 50 , 51 , 52 , 53 ]. Liu et al [ 44 ] also demonstrated that the surface wettability of electrospun composite fiber mats is enhanced by the GO and/or nanohydroxyapatite inclusions.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, tensile strength maintained an acceptable deformation level only when 3 wt% of unmodified MMT was considered, while HT, even at the same lower amount, strongly decreased the ductility of the matrix. It has been reported [50] that a dye−clay nanopigment, synthesized via a cationic exchange reaction between mineral nanoclays and organic dyes, can be considered to gain the advantages of nanoclay reinforcement and colorant features, simultaneously. Nevertheless, even if the dispersion in polymer matrices can offer superior colorimetric properties and color fastness compared to the inorganic counterparts, mechanical enhancement can be obtained only if the nanopigment has been properly intercalated or exfoliated in the formulation.…”
Section: Bionanocomposites With Lemon Hybrid Pigmentsmentioning
confidence: 99%
“…The authors reported the potential use of these starch-based nanocomposites as food packaging materials [69]. Colored biodegradable dye (methylene blue)-clay (montmorillonite)-nanopigment (DCNP)polylactic acid (PLA) nanocomposite films were prepared and tested for various functional properties by Mahmoodi et al [70]. The PLA-DCNP films exhibited high mechanical strength, barrier properties, blocking effect against destructive radiation, biodegradability properties, and potential food packaging applications [70].…”
Section: Food Packagingmentioning
confidence: 99%